FLEXIBLE PAVEMENT THICKNESS ANALYSIS ON KOTO BARU ROAD, PANCUNG DISTRICT, PESISIR SELATAN REGENCY - Armizoprades, Armizoprades; Hafis Maulana; Hervandi M (Journal of Scientech Research and Development, 2025)
On the Koto Baru road section, Pancung Soal District, Pesisir Selatan Regency, there is quite severe road damage that disrupts traffic activities in the area. The volume of vehicles passing through the road can no longer be accommodated by the existing pavement. The researcher aims to analyze the thickness of the pavement layer that is efficient in accommodating the current volume of vehicles and the next few years. By using the 1987 Highways Component Analysis Method and quantitative research type, a survey was conducted on traffic conditions, soil conditions and local rainfall conditions which were then processed using the 1987 Highways Component Analysis method with reference to the current technical standards. The conclusion of this study is the thickness of the surface layer, the upper foundation layer and the lower foundation layer which are technically capable of accommodating the load on the current traffic volume and during the design life.